Quaternary Activity of the Beihewan Fault in the Southeastern Beishan Wrench Belt, Western China: Implications for Crustal Stability and Intraplate Earthquake Hazards North of Tibet. Issue 12 (7th December 2019) - Yang, Haibo; Yang, Xiaoping; Zhan, Yan; Cunningham, Dickson; Zhao, Lingqiang; Sun, Xiangyu; Hu, Zongkai; Huang, Xiongnan; Huang, Weiliang; Miao, Shuqing
Abstract: We present evidence for the Late Quaternary activity of the Beihewan Fault (BHWF), along the southeastern margin of the Beishan block, western China. Field observations and analysis of UAV‐derived DEMs and Google Earth images reveal an 10‐km‐long active fault trace in a region previously considered tectonically inactive. Offset landforms and trench exposures reveal that the fault is dominantly strike‐slip, with local thrust or normal displacements. Average rates of left‐lateral motion and thrusting since the Holocene are estimated to be 2.69 and 0.35 mm/a, respectively. The most recent surface‐rupturing event generated 2.5 m of strike‐slip offset since 6.2–8.6 ka; with estimated M = 6.3–6.9. Modeling and two‐dimensional inversion of new magnetotelluric data indicate that the BHWF is a subvertical low‐resistivity zone that penetrates into the lower crust. Existing geological and geophysical evidence do not support subsurface linkage between the BHWF and Altyn Tagh–Jinta‐Nanshan Fault system further south in the Hexi Corridor. Close examination of high‐resolution satellite imagery west and east of the BHWF reveals other Quaternary surface fault scarps, pressure ridges, offset drainages, and truncated lithological strike belts. Collectively, these features constitute a previously unrecognized 150‐km‐long sinistral deforming belt along the southeastern Beishan and northern Hexi Corridor boundary that we call the Southeast Beishan Wrench Belt. Recognition of Quaternary activity along the BHWF within the larger Southeast Beishan Wrench Belt challenges long‐held assumptions that the Beishan region is a relatively stable and tectonically inactive block within the Late Cenozoic Indo‐Eurasian deformation field north of Tibet. Key Points: The Beihewan Fault (BHWF) is a late Pleistocene‐Holocene left‐lateral strike‐slip fault along the southern margin of the Beishan block MT 2‐D inversion indicates that the BHWF is a steep conductive zone that penetrates the lower crust separate from the Altyn Tagh Fault system The BHWF is part of a newly identified wrench belt north of the Hexi Corridor that likely poses a previously unrecognized seismic hazard